2020
DOI: 10.1037/pha0000349
|View full text |Cite
|
Sign up to set email alerts
|

Context and craving among individuals with alcohol use disorder attempting to moderate their drinking.

Abstract: Many individuals with alcohol use disorder (AUD) prefer a goal of moderation, because they do not see their drinking as causing severe enough consequences to merit abstinence. Given that individuals attempting to moderate will continue to put themselves in contexts where drinking occurs, understanding how distinct external alcohol cues prompt craving is important for implementing the optimal treatments for individuals with AUD. Using data from a randomized controlled trial of stepped care brief interventions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 44 publications
(64 reference statements)
1
19
1
Order By: Relevance
“…The present study aimed to (a) examine synergistic effects of cue exposure and alcohol exposure (i.e., postdrinking status) on craving in the natural environment and (b) test the extent to which these effects are moderated by individual differences in sensitivity to alcohol’s effects (Fleming et al, 2021; Trela et al, 2018). Consistent with findings from prior laboratory (e.g., de Wit & Chutuape, 1993; Kirk & de Wit, 2000; Litt & Cooney, 1999; Manchery et al, 2017; Monti et al, 1993; Ramirez et al, 2015a, 2015b) and field-based studies (Fatseas et al, 2015; Kuerbis et al, 2020; Miranda et al, 2014; Ramirez & Miranda, 2014; Schoenmakers & Wiers, 2010; Trela et al, 2018; Treloar Padovano & Miranda, 2021), craving in the natural environment was increased after cue exposure and during drinking episodes.…”
Section: Discussionsupporting
confidence: 84%
“…The present study aimed to (a) examine synergistic effects of cue exposure and alcohol exposure (i.e., postdrinking status) on craving in the natural environment and (b) test the extent to which these effects are moderated by individual differences in sensitivity to alcohol’s effects (Fleming et al, 2021; Trela et al, 2018). Consistent with findings from prior laboratory (e.g., de Wit & Chutuape, 1993; Kirk & de Wit, 2000; Litt & Cooney, 1999; Manchery et al, 2017; Monti et al, 1993; Ramirez et al, 2015a, 2015b) and field-based studies (Fatseas et al, 2015; Kuerbis et al, 2020; Miranda et al, 2014; Ramirez & Miranda, 2014; Schoenmakers & Wiers, 2010; Trela et al, 2018; Treloar Padovano & Miranda, 2021), craving in the natural environment was increased after cue exposure and during drinking episodes.…”
Section: Discussionsupporting
confidence: 84%
“…For instance, research is indicated that contrasts romantic and platonic relationships, same and mixed‐gender interactions, and more generally, relationships differing in degree of familiarity. Moreover, it will be important to explore how subjective effects of alcohol and other drinking‐related experiences (e.g., alcohol cravings) differ according to solitary vs. social contexts among both social drinkers and those struggling with alcohol use disorder (Creswell, 2021; Kuerbis et al, 2020). Such studies hold promise for developing more comprehensive models of alcohol use disorder etiology and psychotherapeutic treatments that embrace the social nature of alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Our results largely support prior EMA studies that highlight the importance of contextual effects on drinking behavior (Freisthler, Lipperman-Kreda, Bersamin, & Gruenewald, 2014; Ray et al, 2010). For example, drinking in groups and/or in contexts with drinking cues has been shown to increase craving for alcohol and alcohol consumption (Kuerbis et al, 2020; O’Donnell et al, 2019; Trela et al, 2018). Overall, our results suggest that stimulating responses to alcohol may depend on the context, particularly the social context, in which one drinks.…”
Section: Discussionmentioning
confidence: 99%